Impaired localisation and transport function of canalicular Bsep in taurolithocholate induced cholestasis in the rat. Issue 8 (15th July 2003) - Crocenzi, F A; Mottino, A D; Sánchez Pozzi, E J; Pellegrino, J M; Rodríguez Garay, E A; Milkiewicz, P; Vore, M; Coleman, R; Roma, M G
Abstract : Background: Taurolithocholate induced cholestasis is a well established model of drug induced cholestasis with potential clinical relevance. This compound impairs bile salt secretion by an as yet unclear mechanism. Aims: To evaluate which step/s of the hepatocellular bile salt transport are impaired by taurolithocholate, focusing on changes in localisation of the canalicular bile salt transporter, Bsep, as a potential pathomechanism. Methods: The steps in bile salt hepatic transport were evaluated in rats in vivo by performing pharmacokinetic analysis of 14 C taurocholate plasma disappearance. Bsep transport activity was determined by assessing secretion of 14 C taurocholate and cholyl-lysylfluorescein in vivo and in isolated rat hepatocyte couplets (IRHC), respectively. Localisation of Bsep and F-actin were assessed both in vivo and in IRHC by specific fluorescent staining. Results: In vivo pharmacokinetic studies revealed that taurolithocholate (3 μmol/100 g body weight) diminished by 58% canalicular excretion and increased by 96% plasma reflux of 14 C taurocholate. Analysis of confocal images showed that taurolithocholate induced internalisation of Bsep into a cytosolic vesicular compartment, without affecting F-actin cytoskeletal organisation. These effects were reproduced in IRHC exposed to taurolithocholate (2.5 μM). Preadministration of dibutyryl-cAMP, which counteracts taurolithocholate induced impairment in bile salt secretory function in IRHC, restored Bsep localisation in this model. Furthermore, when preadministered in vivo, dibutyryl-cAMP accelerated recovery of both bile flow and bile salt output, and improved by 106% the cumulative output of 14 C taurocholate. Conclusions: Taurolithocholate impairs bile salt secretion at the canalicular level. Bsep internalisation may be a causal factor which can be prevented by dibutyryl-cAMP.